2010
DOI: 10.1093/bjsw/bcq073
|View full text |Cite
|
Sign up to set email alerts
|

Managing Loss and a Threatened Identity: Experiences of Parents of Children Growing Up in Foster Care, the Perspectives of their Social Workers and Implications for Practice

Abstract: Anglia. She has a special research interest in family placement and has published widely on foster-care, attachment and permanence. Bente Moldestad is a clinical social worker and a researcher in 'The Norwegian Longitudinal Study on Out-of-Home Care' in the Child Protection Unit, Uni Research, University of Bergen. She has published a range of articles on parents of children in foster care and kinship care. Dr Ingrid Höjer is Associate Professor in the Department of Social Work, University of Gothenburg. Her m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
109
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(124 citation statements)
references
References 12 publications
9
109
0
5
Order By: Relevance
“…The study findings indicate several key experiences that consolidate into a general narrative, which includes different poles of intense feelings of helplessness and control, loss and meaning, acceptance and guilt. The findings of this study reinforce those of other studies (e.g., Haagenstad, 1992;Schofield, et al, 2010), creating a solid basis for understanding how the parents perceive the effect of the children's removal from home.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The study findings indicate several key experiences that consolidate into a general narrative, which includes different poles of intense feelings of helplessness and control, loss and meaning, acceptance and guilt. The findings of this study reinforce those of other studies (e.g., Haagenstad, 1992;Schofield, et al, 2010), creating a solid basis for understanding how the parents perceive the effect of the children's removal from home.…”
Section: Discussionsupporting
confidence: 87%
“…In a study in Israel, Jaffe (1976) reported that most of the parents perceived the arrangement as necessary, in light of their health, economic, and personal problems, as well as their inability to cope with the children, which prevented them from caring for their children at home. Qualitative interviews in a focus group with parents whose children were placed in foster care in England, Norway, and Sweden (Schofield et al, 2010) found a common similarity, including the need to manage feelings of loss, grief and anger and the need to handle the threat of losing their parental identity and status when their children placed in foster care.…”
Section: Parents' Reactions To the Placement Processmentioning
confidence: 99%
“…Reunification may require parents to revisit powerful emotions associated with loss of the child and their sense of responsibility for the original removal, with deep uncertainty about their capacity to adequately resume their parenting role (Schofield et al, 2011). This family confronted many challenges with the return of a child who had been raised outside of the community.…”
Section: Casementioning
confidence: 99%
“…In fact parents are likely to feel that there is an imbalance of rights and this imbalance is against their child's interests as well as their own. Indeed, when a child is removed by the child protection services from parental care, the loss and grief experienced by the parent whose identity as a parent is threatened is acute, as is the child's own experience of trauma (Burgheim, 2005;Schofield et al, 2010). Again any notion of unfair proceedings and imbalance of rights only compounds these feelings.…”
Section: Resultsmentioning
confidence: 99%